2009
DOI: 10.1111/j.1365-2222.2009.03247.x
|View full text |Cite
|
Sign up to set email alerts
|

Cleaved secretory leucocyte protease inhibitor as a biomarker of chymase activity in allergic airway disease

Abstract: Our data indicate that cSLPI reflects chymase activity in AR and asthma. Hence, cSLPI may serve as a biomarker for disease activity and for monitoring the efficacy of novel anti-inflammatory treatments in chymase-mediated diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Recent studies have shown that patients with allergic asthma express substantially higher levels of SLPI compared with healthy controls, and that SLPI may have a role in protecting the airways from asthma-induced inflammation ( Figure 2) [44,45]. Expression of SLPI actually protects against allergic asthma in a mouse ovalbumin model of asthma, and this may be related to the earlier observations that SLPI can block tryptase-induced bronchoconstriction and hyper-responsiveness [46].…”
Section: Slpi Inflammatory Lung Disease and The Female Gendermentioning
confidence: 87%
“…Recent studies have shown that patients with allergic asthma express substantially higher levels of SLPI compared with healthy controls, and that SLPI may have a role in protecting the airways from asthma-induced inflammation ( Figure 2) [44,45]. Expression of SLPI actually protects against allergic asthma in a mouse ovalbumin model of asthma, and this may be related to the earlier observations that SLPI can block tryptase-induced bronchoconstriction and hyper-responsiveness [46].…”
Section: Slpi Inflammatory Lung Disease and The Female Gendermentioning
confidence: 87%
“…Extracellular SLPI can be cleaved by respiratory proteases such as cathepsin L, matrix metalloproteinase 12 (MMP12), and NE, and can serve as a biomarker for airway disease (5,6,30,40,46). It has been shown that cathepsins and MMPs are induced in smokers as well as in chronic cigarette smoke exposure models (9,28).…”
Section: Discussionmentioning
confidence: 99%
“…However, a limitation is the lack of a marker reflecting chymase inhibition in vivo. Belkowski et al 77 demonstrated that cleaved secretory leucocyte protease may be a useful marker of chymase activity in the sputum of asthmatic patients. However, there is no established marker in plasma, which is necessary to evaluate in vivo chymase activity.…”
Section: Role Of Chymase On Pressure Loaded-and Volume Loaded-cardiacmentioning
confidence: 99%